STUDY OF ANALYSIS OF LEGAL PROTECTION OF WOMEN'S RIGHTS FROM THE PERSPECTIVE OF ISLAMIC LAW - Kurniawan, Harry (Antis-Publisher, 2024)
Objective: This study aims to analyze the concept of legal protection of women's rights in Islamic law and compare it with the Indonesian national legal system. Method: The study utilizes library research, with data sourced from scientific journal articles and research reports. Results: The research finds that Islamic law offers legal protection for women in areas such as livelihood, education, inheritance, and household protection. However, gender roles are defined traditionally, with men assuming the role of family heads, and inheritance distribution tends to favor males. In contrast, the Indonesian national legal system focuses on gender equality, providing comprehensive protection, particularly regarding domestic violence and inheritance rights. Despite these advances, challenges remain in implementing women's protection, while Islamic law, though traditional, continues to ensure women's welfare. Novelty: This study highlights the distinct approaches of Islamic law and the Indonesian national legal system, offering insights into the challenges and advancements in protecting women's rights.